The effect of long term weathering on hemp and rapeseed concrete. (May 2020) - Sheridan, Joseph; Sonebi, Mohammed; Taylor, Su; Amziane, Sofiane
Abstract: Two vegetal aggregate types are studied for their performance regarding immersion and outdoor weathering. The most widely researched bio-aggregate to date is hemp shiv; which is used in this study as well as chopped rapeseed straw which is an alternative bio-aggregate widely available in the UK. In this study the binder used is Vicat prompt natural cement as well as a viscosity modifying agent (VMA) admixture. It was found that the hemp aggregate produced the most durable concrete when compared to rapeseed, and the addition of a VMA resulted in a much more durable material for both aggregate types. Organic and inorganic leaching was also investigated, and it was found that the binder and soluble organics were leaching from all of the concrete types. Highlights: The effect of weathering is studied on vegetal concretes with and without a VMA. Both hemp and rapeseed concretes were susceptible to long term weathering. VMA usage increases the resistance of hemp and rapeseed concretes to weathering. Outdoor weathering had no effect on the compressive strength of all mix types. In all mixes, binder and organic compounds were found to have leached over time.